2006
DOI: 10.1097/01.pec.0000195761.97199.37
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia Administration for Acute Abdominal Pain in the Pediatric Emergency Department

Abstract: Children with abdominal pain receive more analgesia when the physician suspects appendicitis, yet only in half of the cases, and only 15% receive opioids. Opioid underdosing happens in a quarter of times it is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 13 publications
1
26
1
Order By: Relevance
“…In addition, underdosing of morphine demonstrated in previous literature persisted in our findings. 6,12,16 Interestingly, a recent survey of Canadian physicians, including those trained in pediatric emergency, pediatrics, emergency, and family medicine, demonstrated substantially higher self-reported rates of analgesic provision in pediatric appendicitis as compared to our findings. 20 In a case of suspected appendicitis, 92.1% of survey respondents reported that they would offer immediate analgesia.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In addition, underdosing of morphine demonstrated in previous literature persisted in our findings. 6,12,16 Interestingly, a recent survey of Canadian physicians, including those trained in pediatric emergency, pediatrics, emergency, and family medicine, demonstrated substantially higher self-reported rates of analgesic provision in pediatric appendicitis as compared to our findings. 20 In a case of suspected appendicitis, 92.1% of survey respondents reported that they would offer immediate analgesia.…”
Section: Discussioncontrasting
confidence: 55%
“…13 Still, practice continues to be suboptimal, given that less than half of all children received an IV opioid. 12,16,17 In our study, IV morphine was provided significantly less frequently to school-aged children as compared to preschool or adolescent. This is in contrast to earlier literature, where younger children have been shown to receive less analgesia for painful conditions.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Goldman and colleagues described this phenomenon, whereby morphine was given more commonly to children with a higher probability of appendicitis. 4 Similarly, a significant number of respondents indicated they would provide immediate oral analgesia to patients who were vomiting or due for surgical consultation. This may reflect a reluctance to provide intravenous opioids as a first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that analgesia is underutilized for acute abdominal pain [1][2][3][4][5] , delayed in its administration, [1][2][3] and dosed insufficiently 1,3 in the emergency department (ED) setting. Compared to adults, children are at particular risk for suboptimal analgesia and have been found to receive analgesia less often.…”
Section: Introductionmentioning
confidence: 99%